2005
DOI: 10.1016/s0002-9440(10)62302-4
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal T-Cell Reactivity against Paternal Antigens in Spontaneous Abortion

Abstract: Mammalian pregnancy is thought to be a state of immunological tolerance. The mechanisms underlying this phenomenon are still poorly understood. Here, we determined whether an inappropriate function of T regulatory (Treg) cells is involved in the pathogenesis of spontaneous abortion. We evaluated spleen and decidual lymphocytes from CBA/J mice undergoing immunological abortion (DBA/2J-mated) or having normal pregnancy (BALB/c-mated) on day 14 of gestation for ex vivo cytokine production after PMA or paternal an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
188
1
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 496 publications
(196 citation statements)
references
References 60 publications
6
188
1
1
Order By: Relevance
“…In the mouse, it has recently been reported that CD4 ϩ CD25 ϩ Tregs expand during pregnancy and are required to prevent immunological rejection of the fetus (14). In another study, Zenclussen et al (15) demonstrated rescue of allogeneic pregnancy upon transfer of Tregs from normal pregnant mice to abortionprone mice. The data in humans are consistent with a similar function for Tregs in mouse pregnancy.…”
Section: Tregs Naturally Arising Cd4mentioning
confidence: 99%
“…In the mouse, it has recently been reported that CD4 ϩ CD25 ϩ Tregs expand during pregnancy and are required to prevent immunological rejection of the fetus (14). In another study, Zenclussen et al (15) demonstrated rescue of allogeneic pregnancy upon transfer of Tregs from normal pregnant mice to abortionprone mice. The data in humans are consistent with a similar function for Tregs in mouse pregnancy.…”
Section: Tregs Naturally Arising Cd4mentioning
confidence: 99%
“…Suppressor T CD8ϩ lymphocytes possessing progesterone receptor and secreting IL-10 and progesterone-induced blocking factor (PIBF) were shown to be another population of regulatory cells [136]. Compared to abortion-prone mice, normal pregnant mice also had elevated numbers of intrathymic CD4ϩC25ϩ as well as IL-10ϩ Treg cells, that could inhibit both proliferation and IFN␥ secretion of effector cells [137]. The depletion of Treg cells provoked pregnancy failure [138].…”
Section: Immunology Of Fetal Allograft Rejection Based On Animal Studiesmentioning
confidence: 99%
“…The depletion of Treg cells provoked pregnancy failure [138]. Transfer of CD4ϩCD25ϩ Treg cells was shown to prevent abortion but exclusively in that situation, when Treg cells originated from normal pregnant mice, suggesting that only Treg cells exposed previously to paternal antigens could exert regulatory activity in vivo [137]. Murine decidual CD4ϩCD25ϩ Treg cells could cooperate with dendritic cells (DCs).…”
Section: Immunology Of Fetal Allograft Rejection Based On Animal Studiesmentioning
confidence: 99%
“…Development of Tregs in the thymus and periphery is dependent on expression of the transcription factor, forkhead box P3 (FoxP3), [3133] and Foxp3 mRNA expression is decreased two-fold in women with primary infertility compared to fertile patients. Likewise, adoptive transfer of Tregs into abortion-prone CBA/J mice alleviates fetal rejection in the mice [34, 35]. Thus, dysregulated Treg activity may contribute to pregnancy loss and/or infertility.…”
mentioning
confidence: 99%